Liberalism and Chinese economic development perspectives from Europe and Asia - edited by Gilles Campagnolo (New York Routledge, 2016)
Liberalism and Chinese Economic Development brings international contributors together in order to consider economic, political, social and legislative aspects of China?s modernization. This volume explores how liberalism is received and perceived, and whether it is adapted or adopted upon the basis of centuries of Chinese civilization and decades of capitalism.
Includes index
Keywords: Economic development--China.